PENGEMBANGAN MULTIMEDIA PEMBELAJARAN SD PADA MATERI MENGENAL ARTI GAMBAR PADA LAMBANG GARUDA PANCASILA TEMA 1 KELAS III SEKOLAH DASAR - Melisa Karomah; Meli Juliana; Ridho Agung Juwantara (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2020)
This multimedia development aims to produce a multimedia product in the form of a valid and effective learning video as a source of learning in elementary schools. This study uses the ADDIE development research method developed by Dick and Carry to design a learning system. The ADDIE development model consists of five stages which include: (1) analysis, (2) design, (3) development, (4) implementation, (5) evaluation. The results of this study are in the form of learning videos for class III Theme 1 material to recognize the meaning of the image on the Garuda Pancasila symbol. The development of elementary school multimedia learning on the material to recognize the meaning of symbols in Pancasia is very important for learning because the position of the media fully serves the learning needs of students, clarifies messages so that they are not too verbalistic, overcomes the limitations of space, time, energy and sensory power, creates a passion for learning, and can interact directly between students and learning resources.